Implementation of an Occupational Safety and Health Management system (A Study of the Implementation of Occupational Safety and Health at PT PLN Indonesia Power, Barrru) - Mukmin Muhammad; Marsuki Marsuki (Postgraduate, University of Mataram, 2023)
This research aims to determine: Implementation of Occupational Safety and Health Management at PT. PLN Indonesia Power, Barru, by collecting data obtained by observation, interviews, documentation. The results of this research show that PLN Indonesia Power UJP PLTU Barru considers it necessary to implement a system occupational safety and health management in every activity carried out. The implementation of an Occupational Safety and Health Management System (SMK3) in a company is basically a requirement stated in Law Number 13 of 2003 concerning Manpower Article 87 that companies are required to implement an Occupational Safety and Health Management System that is integrated with the company's management system. Based on interview procedures, the implementation of occupational safety and health in the work accident prevention and management system at PLN Indonesia Power PLTU Barru OMU has been carried out. Based on Rahmat Kamruddin's presentation as Senior Environmental K3 Supervisor, factors that influence the running of K3 include communication. Communication at work will influence the work process and is even an essential part of it.